Digital platforms and news publishers: uneasy relationship - Iosifidis, Petros (Frontiers in Communication, 2025)
People across the globe increasingly rely on digital platforms to communicate, entertain and access information. Whereas many of these activities were conducted through legacy news media, entities such as Google, Facebook, YouTube and Instagram currently dominate in most national contexts. The business models of digital platforms, their global nature and the pace that digital technologies and services evolve challenge existing regulatory frameworks concerning consumer protection, transparency, and power imbalances, especially in ensuring that substantial market power does not reduce competition in media and advertising services markets. This article deals with regulating relations between digital platforms and news publishers. It discusses recent reforms which respond to the unequal bargaining power between digital platforms and news media publishers. It questions whether tech giants should pay news media for news content that they carry and whether there are guarantees that funds received by news publishers will be reinvested into public interest journalism. By doing so, it examines the competitive impacts and implications of their existing commercial relationships, in particular the role of online advertising in the dissemination and monetisation of news content and the long term impact on the sustainability of the news media sector. It is clear that news media providers and digital platforms are both benefiting from the distribution of news content. However, the digital platforms need to improve the transparency of their operations for news media providers as they have a significant impact on the capacity of news media organisations to build and maintain an audience and derive resources from the media content they produce. Overall, the article asks whether the discourse surrounding digital platform regulation generally, and measures by nation-states to rebalance market relations to the benefit of news publishers, can safeguard public interest journalism, promote reliable information, and promote democracy.